The learning strategies of successful research graduates : A case study on the Phd holders / Dr. Faizah Abdul Majid, Nor Hashima Mohd Sukor, and Fatin Aliana Mohd Radzi - Abdul Majid, Faizah; Mohd Sukor, Nor Hashima (Institute of Research, Development and Commercialization (IRDC), 2008)
The idea to the research came from the university's concern over the increasing attrition rate of research candidates. Each year, the statistic of research candidates who either opted out or were dismissed due to poor performance shows a rise in percentage (IGS, UiTM, 2006). Additionally, relevant literature review seems to support the possibility of discontinuation of programme among the research candidates (Faizah, 2005; Habibah, 2002; Sayed et al, 1998). Several factors have been identified to contribute to the lost of research candidates from the research programme they enrolled in. According to Brown and Atkins (1990), the factors include difficulties with methodological skills, problems of isolation and more serious commitment given outside research among the part-time students. Sayed et al (1998) who-conducted a longitudinal study on the difficulties faced by ten research students provided relevant input for best practices in research supervision. According to them, the candidates in the study were not familiar with the process of conducting research, the methodology involved and the conventions of thesis writing. They further elaborated that these were due to the lack of understanding, uncertainty of the candidates' own capabilities and high level of anxiety. From the previous studies, a common factor why research candidates may not survive their research was their lack of understanding of how the learning process should be when attempting an independent research under the guidance of a supervisor as full fulfillment of a degree. Hence, the present study was conducted with the aim to investigate the demographic profiles and the strategies employed by 76 successful PhD graduates (53% female, 47% male) who completed their studies either abroad or locally. A set of questionnaire which comprise two parts (Part A: Learning Challenges & Strategies, and Part B: Demographic Background) was administered to the respondents who were chosen based on a purposive sampling. The data was analyzed using SPSS version 15. Cronbach's coefficient alpha was utilized to measure internal consistency of the questionnaire. Values .872 and .842 for the learning challenges and learning strategies construct respectively indicated that the instrument was reliable. In summary, a profile of the successful PhD graduates was built. Additionally, their challenges and strategies employed to overcome the challenges were identified. The findings have implications on future entry requirements, training, and the type of support future PhD candidates need.